1990
DOI: 10.1037/0278-7393.16.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Practice schedules and the use of component skills in problem solving.

Abstract: In motor and verbal learning, random practice schedules produce poorer acquisition performance but superior retention relative to blocked practice. We extend this contextual interference effect to the case of learning cognitive procedural skills to be used in problem solving. Subjects in three experiments practiced calculation with Boolean functions. After this acquisition phase, subjects solved problems requiring these procedures. Experiments 1 and 2 demonstrated superior transfer to problem solving for skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 30 publications
7
74
3
Order By: Relevance
“…This technique has mainly been studied in motor tasks (Brady, 1998;Cross, Schmitt, & Grafton, 2007;Guadagnoli & Lee, 2004;Lee & Magill, 1983;Magill & Hall, 1990;Shea & Morgan, 1979;Simon, 2007). However similar findings have been obtained with, for example, procedural tasks (Carlson, 1989;Carlson, Sullivan, & Schneider, 1989;Carlson & Yaure, 1990), cognitive operational tasks, such as interacting with automatic teller machines (Jamieson & Rogers, 2000), language learning (Jacoby, 1978), foreign vocabulary learning (Schneider, Healy, & Bourne, 1998, learning logical rules (Schneider, Healy, Ericsson, & Bourne, 1995), learning problem-solving from worked examples (Paas & Van Merriënboer, 1994), and troubleshooting tasks (De Croock, Van Merriënboer, & Paas, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…This technique has mainly been studied in motor tasks (Brady, 1998;Cross, Schmitt, & Grafton, 2007;Guadagnoli & Lee, 2004;Lee & Magill, 1983;Magill & Hall, 1990;Shea & Morgan, 1979;Simon, 2007). However similar findings have been obtained with, for example, procedural tasks (Carlson, 1989;Carlson, Sullivan, & Schneider, 1989;Carlson & Yaure, 1990), cognitive operational tasks, such as interacting with automatic teller machines (Jamieson & Rogers, 2000), language learning (Jacoby, 1978), foreign vocabulary learning (Schneider, Healy, & Bourne, 1998, learning logical rules (Schneider, Healy, Ericsson, & Bourne, 1995), learning problem-solving from worked examples (Paas & Van Merriënboer, 1994), and troubleshooting tasks (De Croock, Van Merriënboer, & Paas, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…Previous research has shown that when more time is spent exercising new cognitive skills, performance is improved and the cognitive load is reduced (e.g., Ackerman, 1988;Anderson, 1987;Schneider & Shiffrin, 1977). Other research has demonstrated that when the number (or variety) of example problems is small, learning tends to be rapid, but transfer tends to be weak (e.g., Carlson & Yaure, 1990;Gick & Holyoak, 1987). The purpose of this paper was to test these ideas in a controlled setting using an ITS that was manipulated to yield two contrasting leaming environments: "extended" (12 problems per problem set) and "constrained" (3 problems per problem set).…”
Section: Air Force Systems Command Brooks Air Force Base Texas 78235mentioning
confidence: 99%
“…In addition, when the number (or variety) of example problems is small, learning tends to be rapid, but transfer tends to be weak (e.g., Carlson & Yaure, 1990;Gick & Holyoak, 1987).…”
Section: If Practice Makes Perfect What Does Less Practice Make?mentioning
confidence: 99%
“…Previous studies have shown that practicing tasks in a random order is also important in some cognitive learning tasks (Carlson & Yaure, 1990;Hiew, 1977;Lauer, Streby, & Battig, 1976).…”
Section: Methodsmentioning
confidence: 99%